The Development of Arabic Learning Media Based on Android for Senior High School Students - Ahmad Nur Mizan; Muhammad Aridan; Muhammad Akmansyah; Sefti Adelia; Intan Nur Asiyah; Lisa Mar'atus Sholikha (IAIN Salatiga, 2022)
This research applies the Research and Development design that aims to develop a valid, effective and practical Arabic Learning Media android-based Arabic learning media to increase students’ interest in learning Arabic. This research use Borg and Gall procedure. The instrument used in this research is a questionnaire to obtain qualitative and quantitative data which is then analyzed using the assessment category criteria guidelines to determine product quality. Based on the material expert's assessment, the percentage of 93% was obtained, the media expert's assessment obtained a percentage of 94% and the high school Arabic teacher's assessment obtained a percentage of 96%, while the high school students' responses obtained a percentage of 91.62%. This study shows that android-based Arabic learning media on isim dhamir material is feasible to use in the learning process. It can be concluded that the development of android-based Arabic learning media for high school students is very effective in helping Arabic language learning process.